Lithium ion battery electrolyte for silicon negative electrode, lithium ion battery and method
By adding FDBA to the lithium-ion battery electrolyte to regulate the SiO2 layer characteristics to form a stable SEI film, the problems caused by volume expansion and mechanical stress in the lithium-ion battery are solved, and the cycle stability and high-rate performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411951047.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The silicon negative electrode has severe volume expansion and mechanical stress in lithium-ion batteries, resulting in the powderization of the electrode material, the separation of the active material from the current collector, and the unstable growth of the solid electrolyte interface film (SEI), which in turn affects the battery capacity and cycle life.
2-fluoroethoxy-1,3,2-dioxaborcyclopentane-2-amine (FDBA) is used as an additive to regulate the SiO2 layer characteristics on the surface of the silica material in the lithium-ion battery electrolyte to form a stable and protective SEI film.
Effectively inhibit the growth of lithium dendrites, reduce electrochemical polarization, improve cycle stability and high rate performance, and significantly improve the overall performance of silicon negative electrode lithium-ion batteries.
Smart Images

Figure CN119674243A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a lithium ion battery electrolyte and a lithium ion battery and a method for a silicon negative electrode. Background Art
[0002] Lithium-ion batteries have been widely used in portable electronic devices and electric vehicles due to their high energy density and long cycle life. However, existing commercial lithium-ion batteries mainly use carbon materials as negative electrodes, which have limited theoretical capacity (about 372 mAh g - ¹), it is difficult to meet the growing demand for energy density. Silicon (Si) materials have a very high theoretical specific capacity (3590 mAh g - ¹, corresponding to Li 15 Si4), with abundant reserves and low cost, is considered to be a highly promising negative electrode material for the next generation of high energy density lithium-ion batteries. However, the silicon negative electrode has severe volume expansion (>300%) and mechanical stress caused by it during the charge and discharge process, which leads to pulverization of electrode materials, separation of active materials from current collectors, and unstable growth of solid electrolyte interface film (SEI), which ultimately leads to rapid attenuation of battery capacity and shortened cycle life, seriously restricting the practical application of silicon negative electrodes.
[0003] In order to solve the above problems, researchers have proposed a variety of strategies, including: Preparation of nano silicon particles: Nano-sizing can alleviate the stress caused by volume expansion, but it also increases the specific surface area, leading to more side reactions. Development of new binders: Improve the flexibility and bonding strength of the binder to cope with the volume change of silicon materials. Introduce functional electrolyte additives: Form a stable and protective SEI film on the electrode surface to inhibit the occurrence of side reactions. However, there is usually a dense silicon dioxide (SiO2) layer (about 2-5 nm thick) on the surface of commercial silicon nanoparticles. Although this SiO2 layer can enhance the mechanical strength of silicon materials and alleviate volume expansion to a certain extent, its ionic conductivity is low, which will hinder the transmission of lithium ions, especially under high-rate charge and discharge conditions, resulting in increased electrochemical polarization, easier growth of lithium dendrites, and affecting the safety of the battery. At present, there is still controversy about the effect of the SiO2 layer on the performance of silicon negative electrodes. Some studies believe that through electrochemical treatment, the SiO2 layer can be converted into Li with higher ionic conductivity. x SiOᵧ or Li2O, thereby improving battery performance. However, this conversion usually needs to be carried out at a lower current density and is difficult to achieve under high rate conditions. In addition, short-circuiting SiO2 with lithium metal can also effectively convert it into Li4SiO4 or Li2O, but this requires precise control of the degree of pre-lithiation.
[0004] Therefore, there is an urgent need to develop a new and cost-effective method to regulate the properties of the SiO2 layer on the surface of silicon materials and to form a stable and protective SEI film on the surface of the silicon negative electrode to ensure consistent high performance at different thicknesses, especially under high-rate conditions, to effectively inhibit the growth of lithium dendrites and maintain stable operation of the battery. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a lithium-ion battery electrolyte and a lithium-ion battery and a method for a silicon negative electrode, so as to solve the technical problem of how to effectively regulate the characteristics of the SiO2 layer on the surface of the silicon material and form a stable and protective SEI film on the surface of the silicon negative electrode to inhibit the growth of lithium dendrites under high rate conditions and maintain high performance of the battery.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a lithium ion battery electrolyte for a silicon negative electrode, comprising: a lithium salt, an organic solvent and an additive; the additive is 2-fluoroethoxy-1,3,2-dioxaborolane-2-amine.
[0007] Preferably, in the lithium-ion battery electrolyte used for silicon negative electrode, the mass percentage of the additive is 0.05-5wt.%.
[0008] Preferably, the lithium salt includes one or more of LiPF6, LiClO4, LiBF4, LiAsF6, LiTFSI, LiFSI, LiBOB and LiDFOB.
[0009] Preferably, the organic solvent includes one or more of a carbonate solvent, an ether solvent, an ester solvent and a nitrile solvent.
[0010] Further preferably, the carbonate solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
[0011] Further preferably, the carbonate solvent comprises ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7.
[0012] The present invention also discloses a method for preparing the above-mentioned lithium ion battery electrolyte for silicon negative electrode, comprising the following steps: The lithium salt is dissolved in an organic solvent to prepare a basic electrolyte, and then an additive is added and stirred evenly to obtain a lithium ion battery electrolyte for a silicon negative electrode; the additive is 2-fluoroethoxy-1,3,2-dioxaborolan-2-amine.
[0013] The present invention also discloses a lithium-ion battery, comprising: a positive electrode, a negative electrode, a diaphragm and an electrolyte; the electrolyte adopts the lithium-ion battery electrolyte for silicon negative electrode mentioned above; the negative electrode is made of silicon nanoparticles as active material; the material of the positive electrode comprises: one or more of lithium iron phosphate, ternary material, lithium cobalt oxide and lithium manganese oxide; the ternary material is LiNi x Mn y Co z O2, wherein x+y+z=1; the diaphragm is a polyolefin composite membrane.
[0014] Preferably, the particle size of the silicon nanoparticles is 10-100 nm, and the surface of the silicon nanoparticles has a silicon dioxide layer.
[0015] The present invention also discloses a method for preparing the above-mentioned lithium ion battery, comprising the following steps: Using polyvinylidene fluoride as a binder and conductive carbon black as a conductive agent, the positive electrode, negative electrode and separator are assembled into a button battery in a glove box filled with argon gas, and the above-mentioned lithium ion battery electrolyte for silicon negative electrode is injected. After packaging, a lithium ion battery is obtained.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a lithium ion battery electrolyte for silicon negative electrode, comprising: lithium salt, organic solvent and additive; the additive is 2-fluoroethoxy-1,3,2-dioxaborolan-2-amine (FDBA); the lithium ion battery electrolyte for silicon negative electrode can effectively overcome the kinetic barrier brought by the SiO2 layer on the surface of the silicon negative electrode, and form a stable and protective SEI film on the surface of the silicon negative electrode, thereby improving the cycle stability and high rate performance of the silicon negative electrode. The advantages include: effectively regulating the SiO2 layer and constructing a stable SEI film; by adding a new additive FDBA, it is expected to form a SEI film rich in boron and fluorine elements, such as LiF, lithium borate, etc., on the surface of the silicon negative electrode, thereby improving the stability, ionic conductivity and electronic insulation of the SEI film, and effectively inhibiting the occurrence of side reactions. At the same time, FDBA may interact with the SiO2 layer, regulate its characteristics, and facilitate the formation of the subsequent SEI film. Reduce electrochemical polarization: The introduction of FDBA is expected to reduce the electrochemical polarization of silicon negative electrode, especially under high-rate charge and discharge conditions, it can maintain a more stable charge and discharge voltage platform and improve the energy efficiency of the battery. Improve cycle stability: FDBA can promote the formation of a denser, uniform and protective SEI film, effectively inhibit the decomposition of the electrolyte and the side reactions of silicon materials, alleviate the adverse effects of the volume expansion of silicon materials, prevent the electrode material from pulverizing and separating from the current collector, thereby improving the cycle stability of the battery. Improve high-rate performance: The introduction of FDBA is expected to increase the transmission rate of lithium ions and reduce the interface impedance, so that the silicon negative electrode can also show a good capacity retention rate at high current density. Inhibit the growth of lithium dendrites: The stable SEI film can guide the uniform deposition of lithium ions, reduce the nucleation points of lithium dendrites, thereby inhibiting the growth of lithium dendrites and improving the safety of the battery. Potential application prospects: As a new type of additive, FDBA has a unique chemical structure and potential synergistic effects, which is expected to overcome some challenges faced by silicon negative electrodes in existing technologies and provide new solutions for the practical application of high-energy-density lithium-ion batteries.
[0017] Furthermore, in the lithium-ion battery electrolyte used for silicon negative electrode, the mass percentage of the additive is 0.05-5wt.%, to ensure that FDBA can fully play its role in the electrolyte, such as forming a stable SEI film and reducing electrochemical polarization, while avoiding the side effects that may be caused by excessive concentration, such as increased electrolyte viscosity and increased costs.
[0018] Furthermore, the lithium salt includes one or more of LiPF6, LiClO4, LiBF4, LiAsF6, LiTFSI, LiFSI, LiBOB and LiDFOB. A variety of lithium salts are provided to make the preparation of the electrolyte more flexible, and the most suitable lithium salt or lithium salt combination can be selected according to different battery performance requirements and cost considerations, thereby optimizing the overall performance of the battery.
[0019] Further, the organic solvent includes one or more of carbonate solvents, ether solvents, ester solvents and nitrile solvents. A variety of organic solvents are provided for selection, and these solvents play the role of dissolving lithium salts, transmitting lithium ions, and adjusting the viscosity of the electrolyte in the electrolyte. The combined use of multiple solvents can further optimize the performance of the electrolyte, such as improving the ionic conductivity of the electrolyte, reducing the viscosity, and improving the high temperature performance of the battery.
[0020] Furthermore, the carbonate solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate. These solvents are widely used in lithium-ion battery electrolytes and have good solubility and ion transport properties. By selecting a suitable carbonate solvent or combination, the electrochemical performance and safety of the electrolyte can be further optimized.
[0021] Furthermore, the carbonate solvent includes ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7. This is obtained based on a large number of experiments and can ensure that the electrolyte achieves the best balance in terms of ion conductivity, viscosity, wettability, etc., thereby improving the performance of the battery.
[0022] The present invention also discloses a method for preparing the above-mentioned lithium-ion battery electrolyte for silicon negative electrode, comprising the following steps: dissolving lithium salt in an organic solvent to obtain a basic electrolyte, adding an additive, stirring evenly, and obtaining a lithium-ion battery electrolyte for silicon negative electrode; the additive is 2-fluoroethoxy-1,3,2-dioxaborolan-2-amine. This method is easy to operate, has low cost, and can ensure the uniform distribution of the additive (FDBA) in the electrolyte, thereby giving full play to its role in improving the performance of the silicon negative electrode. In addition, as an additive, FDBA has a unique chemical structure and can form a stable and protective SEI film on the surface of the silicon negative electrode, significantly improving the electrochemical performance of the battery.
[0023] The present invention also discloses a lithium-ion battery, comprising: a positive electrode, a negative electrode, a diaphragm and an electrolyte; the electrolyte adopts the lithium-ion battery electrolyte for silicon negative electrode mentioned above; the negative electrode is made of silicon nanoparticles as active material; the material of the positive electrode comprises: one or more of lithium iron phosphate, ternary material, lithium cobalt oxide and lithium manganese oxide; the ternary material is LiNi x Mn y Co zO2, where x+y+z=1; the diaphragm is a polyolefin composite membrane. Silicon nanoparticles as negative electrode materials have the advantage of high specific capacity and can significantly improve the energy density of the battery. At the same time, there are various choices of positive electrode materials, including lithium iron phosphate, ternary materials, etc., which can be selected according to different application requirements to improve the applicability and flexibility of the battery. As a diaphragm, the polyolefin composite membrane has good ion permeability and mechanical strength, which can ensure the safety and stability of the battery.
[0024] Furthermore, the particle size of the silicon nanoparticles is 10-100 nm, and the surface of the silicon nanoparticles has a silicon dioxide layer. It has a higher specific capacity and better cycle performance. At the same time, the silicon dioxide layer on the surface may interact with the FDBA additive to further promote the formation of a stable SEI film and improve the performance of the battery.
[0025] The present invention also discloses a method for preparing the above-mentioned lithium-ion battery, which comprises the following steps: using polyvinylidene fluoride as a binder and conductive carbon black as a conductive agent, assembling the positive electrode, the negative electrode and the diaphragm into a button battery in a glove box filled with argon, injecting the above-mentioned lithium-ion battery electrolyte for the silicon negative electrode, and packaging to obtain a lithium-ion battery. Polyvinylidene fluoride as a binder can ensure the firm bonding of the electrode materials; conductive carbon black as a conductive agent can improve the conductivity of the electrode. Assembling in a glove box filled with argon can avoid the influence of moisture and oxygen in the air on the battery performance. After injecting a special electrolyte, a lithium-ion battery can be obtained by packaging. The battery prepared by this method has excellent electrochemical performance and stability, and the preparation process is simple and controllable, which is conducive to large-scale production and commercial application of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a diagram of the lithium-ion battery electrolyte for silicon negative electrode and the lithium-ion battery assembly preparation process disclosed in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0029] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0030] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0031] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0032] In the present invention, unless otherwise specified, the numerical range "a~b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6~22" means that all real numbers between "6~22" have been listed in this document, and "6~22" is just an abbreviation of these numerical combinations.
[0033] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0034] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0035] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0036] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0037] The present invention provides a method for preparing a lithium ion battery electrolyte for a silicon negative electrode, comprising the following steps: A certain amount of LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio 3:7) to prepare a 1 M LiPF6 basic electrolyte. Different masses of FDBA were added to the basic electrolyte to make the concentrations of 0.05 wt.%, 0.1 wt.%, 0.5 wt.%, 1 wt.%, 2 wt.% and 5 wt.%, respectively, and stirred evenly to obtain lithium-ion battery electrolytes for silicon negative electrodes of different concentrations.
[0038] The invention discloses a lithium ion battery electrolyte for a silicon negative electrode, comprising: a lithium salt and an organic solvent, and further comprising 2-fluoroethoxy-1,3,2-dioxaborolane-2-amine (2-Fluoroethoxy-1,3,2-dioxaborolane-2-amine, referred to as FDBA) as an additive.
[0039] The concentration of FDBA in the electrolyte composition is 0.05-5 wt.%, more preferably 0.1-2 wt.%, and most preferably 0.5 wt.%.
[0040] The lithium salt is selected from one or more of LiPF6, LiClO4, LiBF4, LiAsF6, LiTFSI, LiFSI, LiBOB, and LiDFOB. More preferably, the lithium salt is LiPF6.
[0041] The organic solvent is selected from one or more of carbonate solvents, ether solvents, ester solvents, and nitrile solvents. More preferably, the carbonate solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). More preferably, in the electrolyte composition, the carbonate solvent is a mixed solvent of EC and EMC. The volume ratio of EC to EMC is 3:7.
[0042] Lithium-ion battery assembly The negative electrode sheet was prepared with silicon nanoparticles as the active material, the positive electrode sheet was prepared with lithium iron phosphate (LiFePO4) as the active material, polyvinylidene fluoride (PVDF) was used as the binder, and conductive carbon black was used as the conductive agent. A polyolefin composite membrane was used as the diaphragm. In a glove box filled with argon, the prepared positive electrode sheet, negative electrode sheet and diaphragm were assembled into a button cell (CR2032). The lithium ion battery electrolyte for silicon negative electrode prepared in Example 1 with different concentrations and the lithium ion battery electrolyte for silicon negative electrode without FDBA were injected respectively, and after packaging, a lithium ion battery was obtained.
[0043] Application of lithium ion battery electrolyte for silicon negative electrode in preparation of lithium ion battery The lithium-ion battery includes a positive electrode, a negative electrode, a separator and an electrolyte. The electrolyte is a lithium-ion battery electrolyte for a silicon negative electrode, and the negative electrode contains a silicon material.
[0044] Preferably, the silicon material is silicon nanoparticles. Preferably, the particle size of the silicon nanoparticles is 10-100 nm. Preferably, the surface of the silicon nanoparticles has a silicon dioxide layer.
[0045] Preferably, the positive electrode material is selected from lithium iron phosphate (LiFePO4), ternary material (LiNi x Mn y Co z O2, wherein x+y+z=1), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMnO4) or more.
[0046] FDBA interacts with the SiO2 layer on the surface of the silicon negative electrode, regulating its characteristics and facilitating the subsequent formation of the SEI film. This interaction may change the structure and properties of the SiO2 layer, making it more conducive to the stable growth of the SEI film. The introduction of FDBA leads to the formation of a SEI film rich in boron and fluorine elements. These elements play a key role in the SEI film, improving the stability, ionic conductivity and electronic insulation of the film. By reducing electrochemical polarization, improving cycle stability and improving high-rate performance, FDBA significantly improves the overall performance of silicon negative electrode lithium-ion batteries.
[0047] As a new type of additive, FDBA has a unique chemical structure and potential synergistic effects. It is expected to overcome some challenges faced by silicon anodes in existing technologies, such as poor cycle stability, poor high-rate performance, and lithium dendrite growth. It provides a new solution for the practical application of high-energy-density lithium-ion batteries and may promote the further development of lithium-ion battery technology.
[0048] The present invention discloses a lithium ion battery electrolyte containing 2-fluoroethoxy-1,3,2-dioxaborolan-2-amine (FDBA) additive. The electrolyte can effectively regulate the SiO2 layer on the surface of the silicon negative electrode to form a stable and protective SEI film, significantly reduce electrochemical polarization, improve cycle stability and high-rate performance, and inhibit lithium dendrite growth, thereby providing a new solution for the practical application of silicon negative electrode lithium ion batteries.
[0049] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0050] Example 1 A method for preparing a lithium ion battery electrolyte for a silicon negative electrode comprises the following steps: A certain amount of LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio 3:7) to prepare a 1 M LiPF6 basic electrolyte. A certain amount of FDBA was added to the basic electrolyte to a concentration of 0.05 wt.%, and the mixture was stirred evenly to obtain a 0.05 wt.% FDBA-containing lithium-ion battery electrolyte for silicon negative electrode.
[0051] Lithium-ion battery assembly The negative electrode sheet was prepared using silicon nanoparticles as the active material, the positive electrode sheet was prepared using lithium iron phosphate (LiFePO4) as the active material, polyvinylidene fluoride (PVDF) was used as the binder, and conductive carbon black was used as the conductive agent. A polyolefin composite membrane was used as the diaphragm. In a glove box filled with argon, the prepared positive electrode sheet, negative electrode sheet and diaphragm were assembled into a button cell (CR2032). The lithium ion battery electrolyte for the silicon negative electrode prepared in Example 1 was injected respectively.
[0052] Electrochemical performance testing of lithium-ion batteries The assembled button cells are subjected to charge and discharge tests, cycle performance tests and rate performance tests.
[0053] See also Figure 1 The figure is a process diagram of the lithium ion battery electrolyte for silicon negative electrode and the lithium ion battery assembly preparation disclosed in Example 1 of the present invention; as can be seen from the figure, LiPF6 is dissolved in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) to prepare a basic electrolyte, FDBA is added to the basic electrolyte, and stirred evenly to obtain a lithium ion battery electrolyte for silicon negative electrode containing FDBA, the prepared positive electrode sheet, negative electrode sheet and diaphragm are assembled into a button battery, the lithium ion battery electrolyte for silicon negative electrode is injected, and after packaging, a lithium ion battery is obtained, and the electrochemical performance of the prepared lithium ion battery is tested.
[0054] Example 2 A method for preparing a lithium ion battery electrolyte for a silicon negative electrode comprises the following steps: A certain amount of LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio 3:7) to prepare a 1 M LiPF6 basic electrolyte. A certain amount of FDBA was added to the basic electrolyte to a concentration of 0.1 wt.%, and stirred evenly to obtain a 0.1 wt.% concentration of FDBA-containing lithium-ion battery electrolyte for silicon negative electrode.
[0055] Lithium-ion battery assembly The negative electrode sheet was prepared using silicon nanoparticles as the active material, the positive electrode sheet was prepared using lithium iron phosphate (LiFePO4) as the active material, polyvinylidene fluoride (PVDF) was used as the binder, and conductive carbon black was used as the conductive agent. A polyolefin composite membrane was used as the diaphragm. In a glove box filled with argon, the prepared positive electrode sheet, negative electrode sheet and diaphragm were assembled into a button cell (CR2032). The lithium ion battery electrolyte containing FDBA for silicon negative electrode prepared in Example 2 was injected respectively.
[0056] Electrochemical performance testing of lithium-ion batteries The assembled button cells are subjected to charge and discharge tests, cycle performance tests and rate performance tests.
[0057] Example 3 A method for preparing a lithium ion battery electrolyte for a silicon negative electrode comprises the following steps: A certain amount of LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio 3:7) to prepare a 1 M LiPF6 basic electrolyte. A certain amount of FDBA was added to the basic electrolyte to a concentration of 0.5 wt.%, and stirred evenly to obtain a 0.5 wt.% concentration of FDBA-containing lithium-ion battery electrolyte for silicon negative electrode.
[0058] Lithium-ion battery assembly The negative electrode sheet was prepared using silicon nanoparticles as the active material, the positive electrode sheet was prepared using lithium iron phosphate (LiFePO4) as the active material, polyvinylidene fluoride (PVDF) was used as the binder, and conductive carbon black was used as the conductive agent. A polyolefin composite membrane was used as the diaphragm. In a glove box filled with argon, the prepared positive electrode sheet, negative electrode sheet and diaphragm were assembled into a button cell (CR2032). The lithium ion battery electrolyte containing FDBA for silicon negative electrode prepared in Example 3 was injected respectively.
[0059] Electrochemical performance testing of lithium-ion batteries The assembled button cells are subjected to charge and discharge tests, cycle performance tests and rate performance tests.
[0060] Example 4 A method for preparing a lithium ion battery electrolyte for a silicon negative electrode comprises the following steps: A certain amount of LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio 3:7) to prepare a 1 M LiPF6 basic electrolyte. A certain amount of FDBA was added to the basic electrolyte to a concentration of 1 wt.%, and stirred evenly to obtain a 1 wt.% concentration of FDBA-containing lithium-ion battery electrolyte for silicon negative electrode.
[0061] Lithium-ion battery assembly The negative electrode sheet was prepared using silicon nanoparticles as the active material, the positive electrode sheet was prepared using lithium iron phosphate (LiFePO4) as the active material, polyvinylidene fluoride (PVDF) was used as the binder, and conductive carbon black was used as the conductive agent. A polyolefin composite membrane was used as the diaphragm. In a glove box filled with argon, the prepared positive electrode sheet, negative electrode sheet and diaphragm were assembled into a button cell (CR2032). The lithium ion battery electrolyte containing FDBA for silicon negative electrode prepared in Example 4 was injected respectively.
[0062] Electrochemical performance testing of lithium-ion batteries The assembled button cells are subjected to charge and discharge tests, cycle performance tests and rate performance tests.
[0063] Example 5 A method for preparing a lithium ion battery electrolyte for a silicon negative electrode comprises the following steps: A certain amount of LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio 3:7) to prepare a 1 M LiPF6 basic electrolyte. A certain amount of FDBA was added to the basic electrolyte to a concentration of 2 wt.%, and stirred evenly to obtain a 2 wt.% concentration of FDBA-containing lithium-ion battery electrolyte for silicon negative electrode.
[0064] Lithium-ion battery assembly The negative electrode sheet was prepared using silicon nanoparticles as the active material, the positive electrode sheet was prepared using lithium iron phosphate (LiFePO4) as the active material, polyvinylidene fluoride (PVDF) was used as the binder, and conductive carbon black was used as the conductive agent. A polyolefin composite membrane was used as the diaphragm. In a glove box filled with argon, the prepared positive electrode sheet, negative electrode sheet and diaphragm were assembled into a button cell (CR2032). The lithium ion battery electrolyte containing FDBA for silicon negative electrode prepared in Example 5 was injected respectively.
[0065] Electrochemical performance testing of lithium-ion batteries The assembled button cells are subjected to charge and discharge tests, cycle performance tests and rate performance tests.
[0066] Example 6 A method for preparing a lithium ion battery electrolyte for a silicon negative electrode comprises the following steps: A certain amount of LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio 3:7) to prepare a 1 M LiPF6 basic electrolyte. A certain amount of FDBA was added to the basic electrolyte to a concentration of 5 wt.%, and stirred evenly to obtain a 5 wt.% concentration of FDBA-containing lithium-ion battery electrolyte for silicon negative electrode.
[0067] Lithium-ion battery assembly The negative electrode sheet was prepared using silicon nanoparticles as the active material, the positive electrode sheet was prepared using lithium iron phosphate (LiFePO4) as the active material, polyvinylidene fluoride (PVDF) was used as the binder, and conductive carbon black was used as the conductive agent. A polyolefin composite membrane was used as the diaphragm. In a glove box filled with argon, the prepared positive electrode sheet, negative electrode sheet and diaphragm were assembled into a button cell (CR2032). The lithium ion battery electrolyte containing FDBA for silicon negative electrode prepared in Example 6 was injected respectively.
[0068] Electrochemical performance testing of lithium-ion batteries The assembled button cells are subjected to charge and discharge tests, cycle performance tests and rate performance tests.
[0069] Example 7 The difference from Example 3 is that the lithium salt is LiClO4 and the organic solvent is propylene carbonate.
[0070] When assembling lithium-ion batteries, the positive electrode material is LiNi x Mn y Co z O2, where X=0.8, y=0.1, z=0.1.
[0071] Example 8 The difference from Example 3 is that the lithium salt is LiBF4 and the organic solvent is dimethyl carbonate.
[0072] When assembling a lithium-ion battery, the positive electrode material is lithium cobalt oxide.
[0073] Example 9 The difference from Example 3 is that the lithium salt is LiAsF6 and the organic solvent is diethyl carbonate.
[0074] When assembling a lithium-ion battery, the positive electrode material is lithium manganese oxide.
[0075] Example 10 The difference from Example 3 is that the lithium salt is LiTFSI, and the organic solvent is an ether solvent ethylene glycol dimethyl ether.
[0076] When assembling lithium-ion batteries, the positive electrode materials are lithium iron phosphate and lithium cobalt oxide.
[0077] Embodiment 11 The difference from Example 3 is that the lithium salt is LiFSI, and the organic solvent is an ester solvent ethylene carbonate.
[0078] When assembling lithium-ion batteries, silicon nanoparticles with a silicon dioxide layer on the surface and a particle size of 10 nm are used as active materials to prepare the negative electrode.
[0079] Example 12 The difference from Example 3 is that the lithium salt is LiBOB, and the organic solvent is acetonitrile, a nitrile solvent.
[0080] When assembling lithium-ion batteries, silicon nanoparticles with a silicon dioxide layer on the surface and a particle size of 20 nm are used as active materials to prepare the negative electrode.
[0081] Example 13 The difference from Example 3 is that the lithium salt is LiDFOB. When assembling lithium-ion batteries, silicon nanoparticles with a silicon dioxide layer on the surface and a particle size of 50 nm are used as active materials to prepare the negative electrode.
[0082] Embodiment 14 The difference from Example 3 is that the lithium salt is LiPF6 and LiClO4. When assembling lithium-ion batteries, silicon nanoparticles with a silicon dioxide layer on the surface and a particle size of 100 nm are used as active materials to prepare the negative electrode.
[0083] In summary, the present invention provides a lithium ion battery electrolyte for silicon negative electrode, a lithium ion battery and a method, the core of which is the addition of 2-fluoroethoxy-1,3,2-dioxaborolan-2-amine (FDBA) as an additive. FDBA can form a SEI film rich in boron and fluorine elements (such as LiF, lithium borate, etc.) on the surface of the silicon negative electrode, thereby improving the stability, ionic conductivity and electronic insulation of the SEI film. This SEI film effectively inhibits the occurrence of side reactions and protects the silicon negative electrode from being corroded by the electrolyte. The introduction of FDBA helps to reduce the electrochemical polarization of the silicon negative electrode, especially under high-rate charge and discharge conditions, and can maintain a more stable charge and discharge voltage platform. The energy efficiency of the battery is improved, so that the battery can still maintain a high performance at high power output. By forming a denser, uniform and protective SEI film, FDBA effectively inhibits the decomposition of the electrolyte and the side reactions of the silicon material. The adverse effects of the volume expansion of the silicon material are alleviated, and the electrode material is prevented from being pulverized and separated from the current collector, thereby significantly improving the cycle stability of the battery. The introduction of FDBA improves the transmission rate of lithium ions and reduces the interface impedance. This allows the silicon negative electrode to show good capacity retention at high current density, meeting the needs of fast charging and discharging. The stable SEI film can guide the uniform deposition of lithium ions and reduce the nucleation points of lithium dendrites. It helps to inhibit the growth of lithium dendrites, improve the safety of the battery, and reduce the risk of short circuit and thermal runaway.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium ion battery electrolyte for silicon negative electrode, characterized in that: include: Lithium salt, organic solvent and additive; the additive is 2-fluoroethoxy-1,3,2-dioxaborolan-2-amine.
2. The lithium-ion battery electrolyte for silicon negative electrode according to claim 1, characterized in that: In the lithium ion battery electrolyte for silicon negative electrode, the mass percentage of the additive is 0.05-5 wt.%.
3. The lithium ion battery electrolyte for silicon negative electrode according to claim 1, characterized in that: The lithium salt includes one or more of LiPF6, LiClO4, LiBF4, LiAsF6, LiTFSI, LiFSI, LiBOB and LiDFOB.
4. The lithium-ion battery electrolyte for silicon negative electrode according to claim 1, characterized in that: The organic solvent includes one or more of carbonate solvents, ether solvents, ester solvents and nitrile solvents.
5. The lithium ion battery electrolyte for silicon negative electrode according to claim 4, characterized in that: The carbonate solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
6. The lithium-ion battery electrolyte for silicon negative electrode according to claim 5, characterized in that: The carbonate solvent includes ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:
7.
7. The method for preparing a lithium-ion battery electrolyte for a silicon negative electrode according to any one of claims 1 to 6, characterized in that: The following steps are involved: The lithium salt is dissolved in an organic solvent to prepare a basic electrolyte, and then an additive is added and stirred evenly to obtain a lithium ion battery electrolyte for a silicon negative electrode; the additive is 2-fluoroethoxy-1,3,2-dioxaborolan-2-amine.
8. A lithium ion battery, characterized in that: include: A positive electrode, a negative electrode, a separator and an electrolyte; the electrolyte is a lithium-ion battery electrolyte for a silicon negative electrode according to any one of claims 1 to 6; The negative electrode is made of silicon nanoparticles as active material; the positive electrode material includes: one or more of lithium iron phosphate, ternary material, lithium cobalt oxide and lithium manganese oxide; the ternary material is LiNi x Mn y Co z O2, wherein x+y+z=1; the diaphragm is a polyolefin composite membrane.
9. The lithium-ion battery according to claim 8, characterized in that: The particle size of the silicon nanoparticles is 10-100 nm, and the surface of the silicon nanoparticles has a silicon dioxide layer.
10. The method for preparing a lithium ion battery according to any one of claims 8 or 9, characterized in that: The following steps are involved: Polyvinylidene fluoride is used as a binder and conductive carbon black is used as a conductive agent. In a glove box filled with argon, a positive electrode, a negative electrode and a separator are assembled into a button battery, and the lithium ion battery electrolyte for silicon negative electrode described in any one of claims 1 to 6 is injected. After packaging, a lithium ion battery is obtained.